Biocontrol Potential of Streptomyces Strain FY4 Against Heterobasidion Root Rot Pathogen In Vitro - Li, Yilin; Li, Xuehai; Geng, Li; Li, Shijie; Gao, Ziwen; Huang, Lin; Vaario, Lu-Min; Sun, Hui (MDPI, 2024)
Root and butt rot, caused by Heterobasidion species, poses a significant threat to coniferous forests in the Northern Hemisphere. Innovative and effective strategies are crucial to enhance the control of this disease. This study aimed at identifying a Streptomyces strain, FY4, and evaluating its biocontrol potential against H. annosum and H. parviporum. Strain FY4 was identified as Streptomyces blastmyceticus based on morphological, physiological, and biochemical characteristics, supported by a multigene phylogenetic analysis using the 16S rRNA, atpD, rpoB, and trpB genes. In vitro dual-culture experiments showed that S. blastmyceticus exhibited antagonistic activity against both H. annosum and H. parviporum, with an inhibition zone diameter exceeding 15 mm. Moreover, the fermentation broth of S. blastmyceticus FY4 displayed significant inhibitory effects on the mycelial growth and spore germination of both Heterobasidion species. At a 10% concentration, the fermentation broth inhibited the mycelial growth by over 90% and reduced the spore germination rate by more than 60%. Additionally, the fermentation broth exhibited significant inhibitory effects on the mycelial growth of four common pathogenic fungi—Phytophthora cinnamomi, P. sojae, Rhizoctonia solani, and Verticillium dahlia, with an inhibition rate over 50%. These findings suggest that S. blastmyceticus FY4 produces antifungal substances capable of effectively suppressing infection of Heterobasidion species in conifers. Consequently, strain FY4 holds great promise as a biological control agent for managing root and butt rot caused by these pathogens, as well as potential for controlling other fungal diseases.
Keywords: antifungal activity; Streptomyces blastmyceticus; strain identification; Heterobasidion spp.